Organisation Management Taking Controlling into Consideration as the Way of Organization Renewal - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Zarządzanie z uwzględnieniem wymagań controllingu jako sposób na odnowę organizacji, 2010)
The aim of this paper is to present controlling as a management improvement and renewal tool, the essence of management function taking into account controlling requirements as well as the benefits resulting from taking into account the controlling rules in organisation management. Taking into consideration especially benefits obtained thanks to the application of this method, controlling may be viewed as a method of support and - at the same time -improvement and renewal of management in its important areas.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 193-204
Keywords: controlling; management improvement; organizational renewal